Rollo Beck: old-school collector, member of an endangered species. - Pitelka, F. A. (1986)
BIB Now: 5585
English
Keywords: HI, EP -- Rollo Beck: old-school collector, member of an endangered species. -- Beck, Rollo; ornithologists, biography -- Beck, Rollo; ornithologo, biografía